Hyponatraemia due to hypothyroidism: a rare side effect from pomalidomide. Issue 3 (2nd March 2021) - Qureshi, Anum; Rhee, Ji Hyun
Abstract : Pomalidomide is an immunomodulatory drug used for relapsed and refractory multiple myeloma (RRMM). Hypothyroidism is an uncommon side effect of pomalidomide. We present a 70-year-old male patient with RRMM on daratumumab, pomalidomide and dexamethasone, who presented with 2 weeks of fatigue. Laboratory values showed sodium of 120 mEq/L, plasma osmolarity of 256 mOsm/kg, urine osmolarity of 648 mOsm/kg and urine sodium of 93 mEq/L. Adrenocorticotropic hormone (ACTH) stimulation test was within normal limits. Thyroid-stimulating hormone (TSH) was 88.6 IU/mL (0.380–4.700 IU/mL), total triiodothyronine (TT3) <21 ng/mL (0.8–2 ng/mL), free thyroxine (fT4) 0.10 ng/dL (0.93–1.70 ng/dL) and free triiodothyronine (fT3) <0.5 pg/mL (2.3–4.2 pg/mL). Antithyroid peroxidase antibody was 726 IU/mL (<9 IU/mL). TSH 1 year ago was 2.88 IU/mL and TT3 was 1.06 ng/mL. He was started on levothyroxine with improvement in his symptoms, sodium level and thyroid functions. The most likely culprit was pomalidomide. Checking thyroid functions before and periodically while on pomalidomide is important in screening for this possible side effect.